2013
DOI: 10.1089/aid.2012.0265
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Women's Participation in a Phase III Community HIV Vaccine Trial in Thailand

Abstract: To assess qualities and outcomes of women participating in a large, community-based HIV vaccine trial, the present study was conducted among female participants of the RV 144 prime-boost trial in Thailand from 2003 to 2009. Qualities of participation refer to complete vaccination, retention, and status change. Outcomes of participation refer to incident rate, adverse event, and participation impact event. A total of 6,334 (38.6%) women participated in the trial, of whom about 50% were classified as low risk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
(38 reference statements)
2
9
0
Order By: Relevance
“…Our analysis revealed that 18% of conceptions among vaccine recipients occurred during the main study phase, though the overall pregnancy rate during study conduct was low (3.09 per 100 w-yr). A similar finding was described in the groundbreaking RV 144 trial in Thailand 18 where 1922 incident pregnancies were recorded in 6334 women (30%) in equal proportions among vaccine and placebo recipients, 362 of those (18%) occurring within the first 6 months of participation 19 . Not surprisingly, younger women aged 25 years and below contributed over 70% of the pregnancies.…”
Section: Discussionsupporting
confidence: 77%
“…Our analysis revealed that 18% of conceptions among vaccine recipients occurred during the main study phase, though the overall pregnancy rate during study conduct was low (3.09 per 100 w-yr). A similar finding was described in the groundbreaking RV 144 trial in Thailand 18 where 1922 incident pregnancies were recorded in 6334 women (30%) in equal proportions among vaccine and placebo recipients, 362 of those (18%) occurring within the first 6 months of participation 19 . Not surprisingly, younger women aged 25 years and below contributed over 70% of the pregnancies.…”
Section: Discussionsupporting
confidence: 77%
“…Most RCTs in this review required women to remain non-pregnant for continuation. 36 40 42 44–48 The majority of studies (n=19) took place in sub-Saharan Africa, most frequently in Kenya (n=8; table 1 ). There were also studies from the Americas (Mexico and the Caribbean) and East Asia (China, Thailand and Cambodia).…”
Section: Resultsmentioning
confidence: 99%
“…There were also studies from the Americas (Mexico and the Caribbean) and East Asia (China, Thailand and Cambodia). All except three 36 44 49 took place in urban settings. The study areas were frequently informal housing settlements, low-income areas or environments known for sex work and/or drug use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations